Antibodies to p53 - can they serve as tumor markers in patients with malignant lymphomas? - Jezeršek Novaković, Barbara (Radiology and oncology (Ljubljana), 2000)
Background. Tumor suppressor gene p53 is mutated in approximately 21% of patients with nonHodgkin's lymphomas (the percentage varying from 0 up to 67% depending upon the histological type). Most of the mutations are point missense mutations resulting in nuclear accumulation of altered protein. Roughly one third of patients with overexpression of p53 protein develop circulating anti p53 antibodies. The present study was aimed at defining the usefulness of serial serological determinations of autoantibodies to p53 for clinical follow up of NHL patients. Patients and methods. Serum levels of antibodies to p53 were determined in various time intervals in three lymphoma patients (who had elevated serum levels at the time of diagnosis) for maximum two years using the commercially available ELISA kit p53-Autoantikoerper ELISA2. Generation. Results. In all three cases the temporal patterns of anti p53 antibodies reflected accurately disease progression or regression, and even foretold a relapse ten months in advance. The reflection of disease regression by autoantibodies lagged approximately three months behind the morphological disappearance of the disease due to a long half life of the antibodies. Conclusion. Our results confirmed the usefulness of antibodies to p53 as tumor markers for follow up of lymphoma patients, yet the subset of patients that could be appropriately followed up with this method is very limited due to the low proportion of patients that develop immune response to p53 protein.
Keywords: Autoantibodies; biokemija; limfom; Lymphoma, non-Hodgkin's; markerji; onkologija; Prognosis; Protein p53; protitelesa; Tumor markers, biological